GIVING A MARRIAGE DOWRY IN JURIDICAL, SOCIOLOGICAL, AND PHILOSOPHICAL PERSPECTIVES - Asrori, Asrori; Ja'far, A.Kumedi; Firdawaty, Linda (Universitas Islam Negeri Raden Intan Lampung, 2024)
The research aims to provide a comprehensive analysis of the obligation to provide dowry in marriage at the time of the marriage contract from a juridical, sociological, and philosophical perspective. This research is normative legal research (Doctrinal Research) with an interdisciplinary approach. The results of the research state that legally dowry is not a pillar of marriage, therefore negligence in its implementation does not cause the marriage to be annulled and valid, however, the dowry must still be given by the prospective husband to the prospective wife either in full or in part in cash or postpone it. Sociologically, because the law is always dynamic, the application of dowry is adjusted to local community habits. The essence is that dowry does not burden men and also does not degrade women. Philosophically, giving a dowry is not just at a transactional and materialistic level, but a dowry is essentially a form of seriousness and love as well as the groom's appreciation for the bride he will marry. Therefore, women must accept the dowry happily as a respect for their dignity and not interpreted as a buying and selling transaction against themselves.